About the Book «SPEECHLESS» by Rosemary Crossley - Zavarzina-Memmi E.G (Moscow State University of Psychology and Education, 2018)
The technique of Facilitated Communication, created by the Australian teacher Rosemary Crossley, is described in her book «SPEECHLESS». Present article is devoted to this book and the issue of facilitated communication, which provides opportunities for communication to non-speaking people with severe multiple developmental disorders, including autism. Translation from English by E.G.Zavarzina-Memmi